The face of Jesus - Lucie-Smith, Edward (New York : Abrams, 2011)
Presents a collection of paintings and images of Jesus throughout the centuries depicting his life, from birth to his crucifixion to his resurrection.
Introduction -- Birth and early life -- The beginning of Christ's mission -- Christ and his followers -- Miracles and compassion -- The passion -- Resurrected Christ -- Christ around the world -- Christ today.
Includes index.
Keywords: Jesus Christ -- Art; Jesus Christ -- Biography; Christian art and symbolism; Jesus Christ -- Art; Jesus Christ -- Biography